Perbedaan Konsep Diri dan Resiliensi Ditinjau dari Jurusan pada Siswa SMK Negeri 1 Merdeka - Evanireni Julietta Purba; Rahmi Lubis; Suryani Hardjo (Mahesa Research Center, 2023)
This study aims to determine differences in self-concept and resilience in terms of majors in students of SMK Negeri 1 Merdeka. The department is part of the Vocational High School, namely the focus of the field of study chosen and studied by students. The disciplines in a department at SMK in this study are Building Engineering and Light Vehicle Engineering. The hypothesis put forward is that there are differences in self-concept and resilience in terms of majors in SMK. In this study, the samples used were 116 students majoring in Building Engineering and 148 students majoring in Light Vehicle Engineering, totaly 264 students. This research uses self-concept scale and resilience scale. The data analysis method is 1 way ANOVA. Based on the data analysis carried out, the results obtained from differences in self-concept in terms of the Department of Building Engineering and Light Vehicle Engineering with a different F value = 513.430; the difference in resilience in terms of the Building Engineering and Light Vehicle Engineering majors obtained a different F value = 615.864 with Sig (p) = 0.000 <0.050, then the proposed hypothesis is declared accepted.